Multiple cooperative systems obtained by powder metallurgy-like processing method: Adenine containing phthalonitrile/graphene/ Fe3O4 high-performance composites with ultra-high EMI shielding - H. Xiao; K. Zeng; J. H. Hu; G. Yang (eXPRESS Polymer Letters, 2021)
Adenine containing phthalonitrile (ADCN)/graphene/Fe3O4 composites with excellent EMI performance, outstanding thermal, thermo-oxidative stability, and heat resistance ae introduced. The interactions between ADCN and nanofillers combined with high-energy ball milling-molding sintering processing method ensure the uniform dispersion of nanofillers in the matrix. The EMI shielding effectiveness (EMI SE) of ADCN/G/Fe3O4 is up to 50 dB with only 0.5 mm thickness, which is one of the best EMI performance compared with previous reports on conductive polymer composites (CPCs). The high-performance ADCN polymer introduces outstanding thermal, thermo-oxidative stability and heat resistance into the composites. The T5% in the air of composites could still maintain more than 491 °C, and the EMI value of composites after flame retardancy test could reach 40 dB. The results prove that ADCN/G/Fe3O4 composite is a promising candidate that could be used in the aerospace industry and under extreme working conditions.